2019
DOI: 10.3390/min9030166
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Evolution of Nb-Ta Oxides and Cassiterite in Phosphorus-Rich Albite-Spodumene Pegmatites in the Kangxiwa–Dahongliutan Pegmatite Field, Western Kunlun Orogen, China

Abstract: The Kangxiwa–Dahongliutan pegmatite field in the Western Kunlun Orogen, China contains numerous granitic pegmatites around a large granitic pluton (the Dahongliutan Granite with an age of ca. 220 to 217 Ma), mainly including barren garnet-, tourmaline-bearing pegmatites, Be-rich beryl-muscovite pegmatites, and Li-, P-rich albite-spodumene pegmatites. The textures, major element contents, and trace element concentrations of columbite-group minerals (CGM) and cassiterite from three albite-spodumene pegmatites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…In this case, the lithium aluminosilicate often develops a narrow rim consisting of a fine-grained vermicular quartz-spodumene symplectitic intergrowth (Figure 6c). This texture has also been described in other pegmatites in this pegmatitic field [36] and also in the bodies of the Kangxiwa-Dahongliutan pegmatite field in the Western Kunlun Orogen of China [37]. Note the presence of spodumene between the albite crystal and the petalite aggregates; (b) spodumene+quartz replacement (SQI) of petalite; (c) spodumene crystals with a fine-grained symplectitic quartz-spodumene intergrowth at the contact with neoformed albite.…”
Section: Mineralogy and Geochemistrysupporting
confidence: 74%
“…In this case, the lithium aluminosilicate often develops a narrow rim consisting of a fine-grained vermicular quartz-spodumene symplectitic intergrowth (Figure 6c). This texture has also been described in other pegmatites in this pegmatitic field [36] and also in the bodies of the Kangxiwa-Dahongliutan pegmatite field in the Western Kunlun Orogen of China [37]. Note the presence of spodumene between the albite crystal and the petalite aggregates; (b) spodumene+quartz replacement (SQI) of petalite; (c) spodumene crystals with a fine-grained symplectitic quartz-spodumene intergrowth at the contact with neoformed albite.…”
Section: Mineralogy and Geochemistrysupporting
confidence: 74%
“…The dated CGM grains exhibit oscillatory zoning and/or sector zoning (e.g., Figure 5), similar to typical magmatic CGMs in many granitic pegmatites [25,40,[44][45][46]. Petrographic observations also reveal that columbite is associated with the primary mineral assemblage spodumene + albite + quartz + muscovite in the Li pegmatites (Figure 4).…”
Section: Emplacement Ages Of the Kalu'an LI Pegmatitesmentioning
confidence: 60%
“…For each analysis, signals on the gas background and sample were collected for 10 s and 40 s, respectively. The analytical procedure and the method for the precision test were described in Feng et al [40]. NIST SRM 610 and NIST SRM 612 were used as the primary and secondary external standards.…”
Section: Methodsmentioning
confidence: 99%
“…This model of the genetic linkage between granite plutons and pegmatites, as residual melts derived from fractional crystallization in large-scale granitic plutons (e.g., [19]), is supported by field relationships and petrographic observations, combined with mineralogical, geochemical, and geochronological data in some pegmatite provinces (e.g., [20][21][22]). However, a number of recent geochronological studies revealed large age differences (>10 Ma) between pegmatites and spatially related granites, making their genetic relationship difficult to identify (e.g., [23][24][25]). In these cases, the pegmatites are interpreted to be of anatectic origin, meaning that they crystallized directly from melts formed by a low-degree of partial melting of high-grade metamorphic rocks (e.g., [23][24][25]).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of recent geochronological studies revealed large age differences (>10 Ma) between pegmatites and spatially related granites, making their genetic relationship difficult to identify (e.g., [23][24][25]). In these cases, the pegmatites are interpreted to be of anatectic origin, meaning that they crystallized directly from melts formed by a low-degree of partial melting of high-grade metamorphic rocks (e.g., [23][24][25]). Likewise, in other regions, the observations and data are not conclusive, particularly in pegmatite provinces with overlapping magmatic events, which cannot be resolved by geochronology or where granite plutons are absent (e.g., [26][27][28]).…”
Section: Introductionmentioning
confidence: 99%